Market heterogeneity and the relationship between competition and price dispersion: Evidence from the U.S. airline market. (September 2022) - Howell, Charles; Grifell-Tatjé, Emili
Abstract: Previous studies agree that competition influences price dispersion, however there is disagreement on the direction of the effect. To explain this contradiction in findings we include a measure not typically considered in competitive analysis, the level of market heterogeneity. We find that the response of price dispersion to changes in competition is conditioned by differentiation. When products in a market are homogenous, increasing competition reduces price dispersion, while in a market with heterogeneous products, the same increase in competition increases price dispersion. We include an output attribute index as a control for market heterogeneity and test our method on 73, 981 observations of airfare data from 2002 through 2016. The implication of our findings for policymakers is that the traditional measures of market concentration do not determine the level of competition alone. Decisions on allowing or disallowing mergers should consider market heterogeneity, not just concentration. The results of this work contribute toward extending knowledge on the effect of competition on price dispersion and introduce a method of measuring market differentiation. Highlights: There are contradictions in previous studies of the effect of competition on price dispersion. To resolve these contradictions we introduce an index that measures the degree of product differentiation in a market. We find that the response of price dispersion is conditioned by the level product differentiation in a market. Competition reduce price dispersion in markets with homogenous products, but increases it in more heterogeneous markets. We highlight how our findings and the index can be used by regulators and policymakers.